2012
DOI: 10.1007/s00261-012-9950-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating hepatocellular carcinoma from dysplastic nodules at gadobenate dimeglumine-enhanced hepatobiliary-phase magnetic resonance imaging

Abstract: DPI is helpful in differentiating HCCs and HGDNs from LGDNs. Demonstration of hypointensity on DPI should raise the suspicion of HGDN or hypovascular HCC in the case of nodules with atypical dynamic pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Besides, the distinction between HGDNs and welldifferentiated HCCs is often problematic and sometimes impossible, even histologically [18,31] (particularly when FNB/ CNB rather than surgery is performed), and these two entities are to be recognized as a continuum rather than individual discrete states [24]. These observations support the value of the differential diagnosis between the group obtained by unifying HCCs and HGDNs and the group of LGDNs, which has already been used in the literature [32,33]. When analyzing [34,35] investigating the utility of DWI and DPI together in the diagnosis of FLLs in the cirrhotic liver, none of which analyzed the value of the lesion-to-liver ADC ratio and the distinction between HGDNs and LGDNs.…”
Section: Discussionsupporting
confidence: 55%
“…Besides, the distinction between HGDNs and welldifferentiated HCCs is often problematic and sometimes impossible, even histologically [18,31] (particularly when FNB/ CNB rather than surgery is performed), and these two entities are to be recognized as a continuum rather than individual discrete states [24]. These observations support the value of the differential diagnosis between the group obtained by unifying HCCs and HGDNs and the group of LGDNs, which has already been used in the literature [32,33]. When analyzing [34,35] investigating the utility of DWI and DPI together in the diagnosis of FLLs in the cirrhotic liver, none of which analyzed the value of the lesion-to-liver ADC ratio and the distinction between HGDNs and LGDNs.…”
Section: Discussionsupporting
confidence: 55%
“…In humans, 95% of the dose of Gd-BOPTA are excreted in urine and only approximately 3%-5% of the dose are excreted into bile[8,22]. Although Gd-BOPTA through the liver metabolism is little, its hepatic elimination is slow and it can maintain the liver enhancement for 40 to 120 min[23]. Previous research findings have indicated that the degree of enhancement of GD-EOB-DTPA decreased as the stage of hepatic fibrosis progressed[24].…”
Section: Discussionmentioning
confidence: 99%
“…In 14 out of 71 cases (19 %), HCC appears as isointense lesions with wash-out signs. This imaging pattern suggests that tumour neo-angiogenesis starts after the disruption of peri-portal space [19, 20]. The main feature of dysplastic nodules was hypovascular lesion (iso/hypointense) with a loss of signal intensity during the late dynamic phase.…”
Section: Discussionmentioning
confidence: 99%